PEMBUATAN MATERI PRESENTASI DENGAN CANVA UNTUK MATA PELAJARAN BAHASA INGGRIS DI SMK YPUI PARUNG - PURNANINGSIH, PARI; Yunita, Devi; Isnaeni, Resti (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
The canva application is a medium that can support the learning process visually and train students’ visual literacy skills. Canva is an online design that provides various editing tools to create various graphic designs, such as posters, flyers, infographics, banners, invitation cards, presentations, facebook covers, and others, including being a tool editing photos because there is a photo editor, photo filters, photo frames, stickers, icons and grid designs, which is easy to understand even if you are still a beginner. Not only that, Canva can also be accessed via desktop and mobile devices. Thus, users can be creative anytime and anywhere. In everyday life, presentation assignment for students are often chosen by Presentation Material because it can assess students cognitively, affectively, and psychomotorically. Starting from assessing group work, evaluating products, generally in the form of papers and power point files to be presented, speaking skills in front of the class, team cohesion, ability to answer questions, to student behavior during presentations. It’s complete and one more thing is very light because the Presentation Material is all you have to do it sit back, occasionally talk, take your grades, while the students explore the class during the presentation activities. Based on this background, lecturer representatives from the Informatics Engineering study program intend to hold activities aimed at holding training activities for making slides for presentation material for English subjects, using the canva application as a learning medium for Presentation Material at YPUI Vocational School Parung. The solution offered is counseling and training in making presentation slides using the canva application Pamulang University, as a leading campus in the IT field, through this program can provide free training on software processing skills. Participants in this activity were 10-30 people, all of whom were presentation materials at YPUI Vocational School Parung. It is hoped that in the future the limited 10-30 participants can relate learning media in schools. Participants are able to understand how to make interesting slides.Keywords: Technology, Students, Presentation, PKM, Canva